Snail Expression is Positively Correlated with Depth of Invasion in Colorectal Carcinoma - Upik Anderiani Miskad; Fardah Akil; Muhammad Husni Cangara; Haslindah Dahlan; Gina Andyka Hutasoit; Muhammad Riza Ilyasa (Indonesian Biomedical Journal)
BACKGROUND: Colorectal carcinoma ranks as the second deadliest and third most prevalent cancer globally. The depth of tumor invasion and the presence of tumor-infiltrating lymphocytes (TILs) are linked to survival rates in this disease. Meanwhile, Snail expression is positively correlated with tumor grade, recurrence, metastasis and poor prognosis in various tumors. However, not many studies discuss the correlation of Snail expression with invasion depth and TILs in Indonesia. Therefore, this study was conducted to investigate the correlation between Snail expression and both the depth of invasion and TIL scoring in colorectal carcinoma.